ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO LIKUIDITAS PADA BANK KONVENSIONAL (Studi pada Bank yang Termasuk Badan Usaha Milik Pemerintah dan Bank Asing di Indonesia dan Malaysia Periode Tahun 2011 sampai dengan 2015) - Azhary, Alwan; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2017)
The banking system has an important role to play in the real sector because of its function as an intermediary institution which is a financial institution that connects between parties who have excess funds to parties who are in need of funds through financial services. One of focuses on this research is liquidity risk. The purpose of this study is to analyze the effect of non-performing loans, net working capital, return on assets, capital adequacy ratio and size against liquidity risk in conventional banks in Malaysia and Indonesia in 2011-2015.This research using multiple regression analysis and population in this research are banks that included in local and foreign banks which are sorted by using purposive sampling method. The total research population is 32 banks consisting of 24 samples of conventional banks in Indonesia and 8 samples of conventional banks in Malaysia. The results showed that non performing loans and capital adequacy ratio do not affect liquidity risk in both models. While return on assets has a positive and significant impact on liquidity risk of conventional banks in Indonesia and has no effect on conventional banks in Malaysia. Variable net working capital does not affect liquidity risk in conventional banks in Indonesia while banks in Malaysia have positive and significant effect. And variable size has no effect on liquidity risk in Indonesia and has a significant negative effect on conventional banks in Malaysia.